Melatonin Protects HT22 Hippocampal Cells from H2O2-induced Injury by Increasing Beclin1 and Atg Protein Levels to Activate Autophagy - Gao, Qiang; Guo, Xiaocheng; Cao, Yang; Jia, Xiaotong; Xu, Shanshan; Lu, Chunmei; Zhu, Hui (Current Pharmaceutical Design, 2021)
Background: The aging of hippocampal neurons leads to a substantial decline in memory formation, storage and processing. The neuroprotective effect of melatonin has been confirmed, however, its protective mechanism remains unclear. Objective: In this study, mouse hippocampus-derived neuronal HT22 cells were used to investigate whether melatonin protects the hippocampus from hydrogen peroxide (H2O2)-induced injury by regulating autophagy. Methods: Rapamycin (an activator of autophagy) and 3-methyladenine (3MA, an inhibitor of autophagy) were used to induce or inhibit autophagy, respectively. HT22 cells were treated with 200 μM H2O2 in the presence or absence of 50 μM melatonin. Cell counting kit 8 (CCK-8), β-galactosidase and Hoechst staining were used to measure the viability, aging and apoptosis of cells, respectively. Western blot analysis was used to detect the levels of autophagy-related proteins. Results: The activation of autophagy by rapamycin alleviated H2O2-induced oxidative injury, as evidenced by morphological changes and decreased viability, while the inhibition of autophagy by 3MA exacerbated H2O2- induced injury. The inhibitory effect of melatonin on H2O2-induced injury was similar to that of rapamycin. Melatonin also alleviated H2O2-induced aging and apoptosis. Melatonin activated autophagy in the presence or absence of H2O2, as evidenced by an increased Lc3b 14/16 kd ratio and a decreased P62 level. In addition, H2O2 decreased the levels of Beclin1 and Atg5/12/16, which were reversed by rapamycin or melatonin. The effects of melatonin on H2O2-induced injury, autophagy and protein expressions were effectively reversed by 3MA. Conclusion: In conclusion, these results demonstrate that melatonin protects HT22 hippocampal neurons from H2O2-induced injury by increasing the levels of the Beclin1 and Atg proteins to activate autophagy.
Keywords: Beclin1